2010
DOI: 10.1093/gerona/glq095
|View full text |Cite
|
Sign up to set email alerts
|

Improving Precision in Investigating Aging: Why Telomeres Can Cause Problems

Abstract: A host of recent publications has highlighted a growing number of discrepancies between small-scale laboratory-based studies and larger clinical and epidemiological studies, using telomere length as a bio-aging marker for physical, sociological, and psychological parameters in their respective cohorts. These discrepancies may be rooted in differing telomere length measurement methods and their application. This leads to the question of just how robust telomere length is as a biomarker of aging and whether meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 20 publications
1
32
0
Order By: Relevance
“…However, it is also possible that telomere length may primarily be related to illness due to its strong association with chronic stress exposure rather than being a direct cause of illness (15). The use of telomere length as a marker of biological ageing has been criticized, and evidence linking telomere length to functional decline is somewhat equivocal (16,17).…”
Section: Hads Hospital Anxiety and Depression Scalementioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also possible that telomere length may primarily be related to illness due to its strong association with chronic stress exposure rather than being a direct cause of illness (15). The use of telomere length as a marker of biological ageing has been criticized, and evidence linking telomere length to functional decline is somewhat equivocal (16,17).…”
Section: Hads Hospital Anxiety and Depression Scalementioning
confidence: 99%
“…However, it is also possible that telomere length may primarily be related to illness due to its strong association with chronic stress exposure rather than being a direct cause of illness (15). The use of telomere length as a marker of biological ageing has been criticized, and evidence linking telomere length to functional decline is somewhat equivocal (16,17).Over the past few years, a number of studies have found associations between MDD and telomere length; those with long-term MDD have been reported to have shorter telomeres than non-depressed controls. In a middle-aged sample with a variety of mood disorders including MDD, telomeres were significantly shorter among those with mood disorders versus age-matched controls (18).…”
mentioning
confidence: 99%
“…Hence the association between gender and telomere length might vary by age. Whilst telomere length is inversely related to chronological age in humans (Shiels et al, 2011), there are concerns about how robust telomere length is as a biomarker of ageing (Shiels, 2010; Shiels et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Because of the limited sample size and low number of events, we were unable to establish an association between TL elongation and clinical outcomes such as mortality. The latter is not unexpected, as TL is a weak biomarker of aging [19,38] and the observational period of this Japanese cohort was too short to detect a survival advantage of TL. Clearly, our data would benefit from confirmation by using a more robust biomarker of aging, such as CDKN2A.…”
Section: Discussionmentioning
confidence: 73%